Comparing the ignition parameters of promising coal fuels - Vershinina K. Yu. Kseniya Yurievna; Dorokhov V. V. Vadim Valerjevich; Romanov D. S. Daniil Sergeevich; Strizhak P. A. Pavel Alexandrovich (2020, 2020)
Title screen